The structure of Islamic bank through bibliometric analysis. - Muhammad Nadzmi Nazam; Noor Adilah Abdul Aziz; Noor Aida Mohd Halim; Nur Atikah Azmi (2022)
The objective of this paper is to investigate the current trends and structure of research on the determinants of Islamic banking. In addition, the objective of this paper is also to determine the prominent authors and the structure of the collaboration in the topic of Islamic banking. This study presents a review of 282 published documents on the determinant trends of Islamic banks through bibliometric analysis. The document was taken from the Scopus database. Moreover, we filtered the article to get more detailed by selected the year from 2012 until 2021, document type which is article, journal as the source type and last but not least English as a language. We used VOSviewer to run the analysis. Although the latest bibliometric analysis on the topic of the structure of Islamic banks, the methodology used in search terms is limited. This is because of the use of the combined keyword "Islamic bank" and "determinants". For this section, three word combinations with logic operators were used, TITLE-ABS-KEY “Islamic bank” and “determinants”, thus successfully reaching the structure of Islamic bank more widely. Our results show that the leading author and collaborative structure most cited on efficiency is Kamarudin, F. There are three countries that stand out with the largest scientific article production on this topic namely Malaysia, followed by Tunisia and Indonesia. Recent research trends indicate the field of knowledge in financing management. The implementation of the dual banking system which began with the establishment of Islamic banking has given a new impetus to Islamic financial institutions as one of the important needs of consumers, especially Muslim consumers. It impacts positively on the performance of Islamic banking to continue to develop and stabilize through the management of the services system in various sectors to involve the growth of internationalization of Islamic finance.